MindingMe: A Feasibility Study on Conducting Neuroimaging Research Among Diverse Groups. Issue 2 (7th March 2023) - Jones, Lenette M.; Sullivan, Stephen; Cuffee, Yendelela; Monroe, Korrey; Rafferty, Jane; Giordani, Bruno
Abstract : Background: Neuroimaging tools, such as functional magnetic resonance imaging, are useful in understanding differences in brain activity that predict behavior change. Designing interventions based on brain activity and response may enhance current self-management regimens. Yet, diverse groups, such as Black women with chronic illness, have historically been left out of neuroimaging research. Objectives: The aims of this study were to assess (a) the feasibility of conducting neuroimaging research among Black women with hypertension and (b) the predictors of willingness to participate in future studies. Methods: A survey designed to assess interest in participating in neuroimaging research was distributed through a Facebook campaign targeting Metro-Detroit Blacks with hypertension. A 10-minute, 44-item survey queried the women regarding their perspectives related to participation in neuroimaging studies. Logistic regression analyses were conducted to predict willingness to participate in a future study; they included a range of predictors: demographic indicators, history of blood pressure diagnosis, systolic and diastolic blood pressure, and availability of a support person who could accompany the participant to a future study session. Results: Two hundred fifty-seven Black women completed the survey. On average, the women were 59 years old, had been diagnosed with hypertension for 14 years, and had a systolic blood pressure of 141 mmHg. Participants were willing to travel 40 miles to participate, and many preferred to drive a personal vehicle. Some women were claustrophobic (20%) or had metal in their bodies (13%) and, therefore, would likely be ineligible to participate in neuroimaging studies. Some were nervous about the "small space" of a scanner, but others stated they would "enjoy participating" and wanted to "help future people…get well." Women who had a support person to attend their appointment with them were almost 4 times more likely to state they would participate in future studies. Those who had been diagnosed with hypertension for more than 11 years (the median) were almost 3 times more likely to report interest in participating in a future study than those participants who had been diagnosed with hypertension for 11 years or less. Discussion: Black women with hypertension were interested and eligible to participate in neuroimaging research. Despite some of the facilitators and barriers we identified, the women in our sample were interested in participating in future studies. The presence of a support person and length of time with a hypertension diagnosis are important predictors of willingness to participate in a future study.